Estudio de factibilidad para la creación de una empresa especializada en el servicio de capacitación y actualización de norms internacionales de información financiera (NIIF"s) en la ciudad de Loja - Cartuche Valverde, Claudia Vanesa (2016)
This research was developed under the elaboration of a feasibility study for the creation of a company which is specialized in the service of capacitation and upgrade of the International Financial Reporting Standards (IFRS) at Loja city. The specific objectives that have been raised to the effect contemplate the structural framework that makes up a feasibility study. One of the objective is the execution of a market study, which allows determining the offer, demand, and scope of the company specialized in capacitation and upgrade of the IFRS. This goal was accomplished by the application of a survey to 256 companies linked to productive activity, and interviews applied to the respective offer, like the Ecuadorian Vocational Training Service and the College of Counters of Loja. The results found allowed to know, through inductive, analytic and synthetic methods and statistical processing of quantitative data, the general basis of market segmentation, diagnostic and analysis of key factors which influence on the quality of the service delivery; therefore it allows to know the level of positioning, number of applicants or offered, strategies that comply each of the requirements and customer needs. The development of a technical study to determine the exact place where the unit of specialized services will be located, its distribution and necessary equipment for its performance. This objective was developed through the inquiry, analysis and consultation of establishments which are in concordance to the service activity, operative capacity in base to the requirements of the unsatisfied demand, pointing out places corresponding to the central area of the location which denote - 11 - spaces with natural lighting, availability adequacy around distribution equipment required for their development. The design of an administrative, organizational and legal plan of the upcoming company, the objective was accomplished through the analysis and study of administrative documents which are fundamental in the requirements and constitution of this project. As well, the recompilation of bibliographic sources allowed obtaining information about the legality and transaction processes for the corresponding constitution. The achievement of the financial study to determine the factibility and viability of the Project, as one of the most important specific objectives in the project evaluation, was developed through the fieldwork for the determination of required costs in the service operability, a series of assessments, which allowed to highlight the level of sustainability and survival of this project. After the results which were obtained from the development and evaluation of each study, it stands out that the project is a good proposal and solution alternative in front of the requirements demanded of the business environment, also pointing out favorable results for its viability during the estimated time of five years, corresponding to the life of the project study. However it is important to mention the growth of the offer of the service floor with the purpose of ensure the sustainability of the project through time. -